Pilomotor Seizures in a Patient With LGI1 Encephalitis - Yang, Jinxia; Sun, Qiying; Yang, Guang (Frontiers in Neurology, 2020)
Limbic encephalitis (LE) with antibodies against leucine-rich glioma inactivated protein 1 (LGI1) is an autoimmune disease with variable clinical features, including seizures, cognitive disorders, psychiatric disturbances and hyponatremia. The majority of these patients present faciobrachial dystonic seizures (FBDS), which are regarded as characteristic symptom. A few cases have reported pilomotor seizures as the main manifestation of anti-LGI1 encephalitis. Here we described a Chinese woman with frequent pilomotor seizures who was finally diagnosed as anti-LGI1 encephalitis. Our report emphasizes the possible significance of pilomotor seizures in anti-LGI1 encephalitis.